EFEKTIVITAS PENGGUNAAN MEDIA WEB WORDWALL DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SDN 31 KALUPPANG - Angraeni, Ulfa; Syarif, Irman; Danindra, Fuad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the low student learning outcomes in Pancasila Education, particularly on the topic of Indonesian Cultural Diversity, thus requiring the use of innovative learning media. This study aims to determine the effectiveness of using Wordwall web-based media in improving student learning outcomes and to measure the extent of the improvement among fifth-grade students at SDN 31 Kaluppang. This study employed a quantitative approach with a pre-experimental method using a one-group pretest-posttest design, involving 18 students as the research subjects. The data analysis techniques included descriptive analysis, paired sample t-test, and N-Gain test. The results showed an improvement in student learning outcomes, indicated by an increase in the average score from 65.47 in the pretest to 89.12 in the posttest. The N-Gain score was 0.696, which falls into the moderate category, indicating a fairly effective improvement. In addition, the paired sample t-test showed a significance value of 0.000 < 0.05, indicating a significant difference between the pretest and posttest results. Therefore, the use of Wordwall web-based learning media is effective in improving student learning outcomes in Pancasila Education for fifth-grade students at SDN 31 Kaluppang.